PasT of Escherichia coli sustains antibiotic tolerance and aerobic respiration as a bacterial homolog of mitochondrial Coq10. Issue 8 (18th June 2020) - Fino, Cinzia; Vestergaard, Martin; Ingmer, Hanne; Pierrel, Fabien; Gerdes, Kenn; Harms, Alexander
Abstract: Antibiotic‐tolerant persisters are often implicated in treatment failure of chronic and relapsing bacterial infections, but the underlying molecular mechanisms have remained elusive. Controversies revolve around the relative contribution of specific genetic switches called toxin–antitoxin (TA) modules and global modulation of cellular core functions such as slow growth. Previous studies on uropathogenic Escherichia coli observed impaired persister formation for mutants lacking the pasTI locus that had been proposed to encode a TA module. Here, we show that pasTI is not a TA module and that the supposed toxin PasT is instead the bacterial homolog of mitochondrial protein Coq10 that enables the functionality of the respiratory electron carrier ubiquinone as a "lipid chaperone." Consistently, pasTI mutants show pleiotropic phenotypes linked to defective electron transport such as decreased membrane potential and increased sensitivity to oxidative stress. We link impaired persister formation of pasTI mutants to a global distortion of cellular stress responses due to defective respiration. Remarkably, the ectopic expression of human coq10 largely complements the respiratory defects and decreased persister levels of pasTI mutants. Our work suggests that PasT/Coq10 has a central role in respiratory electron transport that is conserved from bacteria to humans and sustains bacterial tolerance to antibiotics. Abstract : Previous work on antibiotic‐tolerant persisters of pathogenic Escherichia coli highlighted the role of PasT, described as a toxin of a toxin–antitoxin system, in their resilience. Here, we show that PasT is not a toxin but rather the bacterial homolog of mitochondrial Coq10 that guides the electron carrier ubiquinone in respiratory electron transport. Consistently, pasT mutants of pathogenic E. coli and Salmonella Typhimurium show pleiotropic phenotypes of defective respiration including impaired persister formation that can largely be complemented by human Coq10.